2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.25046
|View full text |Cite
|
Sign up to set email alerts
|

Volunteerism in Engineering Students and Its Relation to Social Responsibility

Abstract: Addressing how engineering students view their role in society, their social responsibility, is seen as a central aspect toward creating holistic engineers who are able to address complex social issues. The Professional Social Responsibility Development Model (PSRDM) provides a framework for social responsibility development in engineers. Included in this model is a cycle where feelings of professional obligation to help others are enhanced through engaging in service. This study set out to characterize volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…These data are consistent with those observed in other systematic reviews [ 51 ], whose research focused on SL and its interaction with university social responsibility. Only one in 24 studies used a quantitative method [ 96 ]. Willard and Crandall [ 58 ] argue that future researchers should consider the collection of qualitative data in the form of student reflections, as they are already a crucial tool in the study of SL.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with those observed in other systematic reviews [ 51 ], whose research focused on SL and its interaction with university social responsibility. Only one in 24 studies used a quantitative method [ 96 ]. Willard and Crandall [ 58 ] argue that future researchers should consider the collection of qualitative data in the form of student reflections, as they are already a crucial tool in the study of SL.…”
Section: Discussionmentioning
confidence: 99%
“…The PSRDM framework posits that engagement in forms of service is the mechanism through with one's feelings of obligation and desire to help others through their profession deepens. Results have shown that there are strong correlations between engineering student's views of social responsibility and participation in service experiences 9,37 .…”
Section: Social Responsibility In Engineeringmentioning
confidence: 99%
“…in 2-sided test 0.089 from SPSS). Previous research found a correlation between undergraduate engineering student participation in volunteer activities (including a variety of community service activities) and social responsibility scores [21]. This correlation is logical; a higher sense of social responsibility is likely to motivate a student to participate in volunteer activities [16,18].…”
Section: Participation (Or Not) In K-12 Activitiesmentioning
confidence: 94%
“…In previous research, Pickering et al [8] noted "female engineers demonstrate a large interest in [K-12] outreach efforts" (p. 1), and that the engineering college students participating in the outreach program at their institution were 40-60% females (higher than ~32% female students in engineering at the institution). Previous research identified higher participation rates in volunteer activities of female versus male undergraduate engineering students, among 1885 students at 17 universities [21]. More specifically, a higher percentage of female than male engineering students reported tutoring elementary and secondary students (54% vs. 43%, respectively) [21].…”
Section: Participation (Or Not) In K-12 Activitiesmentioning
confidence: 99%